PENGARUH MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, CREATE) TERHADAP KETERAMPILAN BERKOMUNIKASI DAN BERPIKIR TINGKAT TINGGI DALAM PEMBELAJARAN IPAS SEKOLAH DASAR - Silvia Dwi Prastiwi; Rismita; Heni Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model on communication and higher order thinking skills in elementary school science learning on energy transformation. This type of research is quantitative research. The method used in this study is a quasi-experimental design with a non-equivalent control group. The study population was 543 students with a sample of 66 students determined randomly purposive sampling. The data were analyzed using descriptive statistics, normality test, homogeneity test, and hypothesis test in the form of t-test with the help of SPSS versi 29 for windows program. Based on the results of the study on students communication skills, the average postest results of students in the experimental class were 81.15 after being given learning using the RADEC learning model, while in the control class it was 71.67 after being given learning using the lecture model. Meanwhile, based on the results of the study on students higher order thinking skills, the average postest results of students in the experimental class were 82.09 after being given learning using the RADEC learning model, while in the control class it was 71.09 after being given learning using the lecture model. Based on the results of the t-test on students communication skills, it is known that t count is 5.666>t table of 2.000. While the results of the t-test on students higher order thinking skills are known that t count is 3.900>t table of 2.000. Thus, it can be concluded that the RADEC (Read, Answer, Discuss, Explain, and Create) learning model has an influence on communication and high level thinking skills in elementary school science learning.